Environmental assessments in the workplace: an analysis of workplace wellbeing facilities for people of reproductive age - Seonad K Madden; Briony Hill; Andrew P Hills; Helen Skouteris; Claire Blewitt; Kiran DK Ahuja (Sax Institute, 2024)
Objective: To investigate the availability of resources at an Australian university workplace to support the health, wellbeing, and transition to parenthood of female employees working during the preconception, pregnancy, and postpartum periods. Type of program or service: Workplace health promotion for female employees of reproductive age. Methods: A survey of female employees aged 18-45 years evaluated participant health practices, availability of work and parenting supports, and access to health and wellbeing resources in the workplace. Additionally, an environmental assessment was completed by employees with a knowledge of local healthy lifestyle supports and a minimum of 2 years' employment. The assessment documented site characteristics and availability of wellbeing facilities across 10 campuses. Results: There were 241 valid survey responses. Of 221 respondents to a question about workplace support, 76% (n = 168) indicated that the workplace should play a role in supporting the transition to parenthood and in health promotion, with 64.1% of 223 participants disagreeing with the statement "my health is not the responsibility of the university". Both the survey and environmental assessment revealed that access to parenting resources to support employee health and wellbeing were suboptimal. Lessons learnt: There is a misalignment between the needs of female employees working during these health-defining life stages, and the availability of resources to support those needs. Regulatory guidance may be required to navigate resource gaps within the work environment and address factors impacting the health and wellbeing of employees of reproductive age.